A relação entre ciência e ideologia em tempos de hegemonia financeira: a biotecnociência e o mercado de promessas - Leandro Módolo Paschoalotte (Ciências Sociais Unisinos)
From the need to understand the systematic presence, in the most different media of scientific dissemination, of the figuration of the human being as being ontologically equal to other animals, mainly because of their molecular biological characteristics, such as genetic ones. This work seeks to put on the scene a critical theoretical approach about how the social construction of biotechnologies and the scientific discourses that underpin them are biased by subordination to the financial market, making in contemporary society the social relations between science and ideology are resignification. In this sense, through a literature review of the specialized literature and the discourse analysis of central characters of the techno-scientific field on screen, we defend as central argument that the development of the economy around biotechnologies and, underlying it, the emergence of a “market of promises” have made scientific discourses begin to function ideologically as vehicles of capital accumulation.